A survey of information given to head-injured patients on direct discharge from emergency departments in Scotland. Issue 5 (23rd April 2007) - Kerr, Jacques; Swann, Ian J; Pentland, Brian
Abstract : Aim: To survey the information provided to head-injured patients on discharge from emergency departments (EDs) in Scotland. Methods: EDs throughout Scotland were asked to supply a copy of their head injury advice pamphlet for analysis. Each pamphlet was assessed against a template and an Excel spreadsheet was created. Results: All 30 (100%) Scottish EDs responded. The frequency with which specific features appeared varied widely, with most pamphlets concentrating on emergency features, with less emphasis on postconcussion symptoms. Conclusions: Head injury discharge advice should be standardised throughout EDs, with more emphasis given to postconcussion features.